REDEFINING OF DEPENDENT WORK AND ITS SOCIO-LEGAL DIMENSION IN SLOVAK REPUBLIC - Zofcinova, Vladimira (European Scientific Journal, ESJ, 2015)
The dignity of the employees in the performance of dependent work must be the limiting factor that determines the present as well as the future trend of labor law in Slovak Republic. This article is focused on selected aspects of the defined development of dependent work and attention is also paid to the indicators of dependent work. The author refers in further points that the fact that current dependent work legislation of the Slovak Republic and its global peers must create a relative equal level for economic competition with the acceptance of the dignity of man as the executor of work.